A educação, o cenário da pós-modernidade e a questão da normatividade do discurso pedagógico - Lima, João Francisco Lopes de (2009)
The doctoral thesis Education, the scenario of post-modernity and the issue of normativeness of pedagogical discourse inserts itself in the subject of the relations between post-modernity and education, recognizing the failure of the foundations of metaphysical order as the founding structure of the normativeness of pedagogical discourse. The study takes as reflection input the theoretical contribution of the philosophy that acknowledges the post-modern scenario, taking particularly the contribution of Lyotard, Vattimo and Habermas on the symptoms of the modernity crisis and the emergence of post-modernity and its implications for the constitution of the normativeness of pedagogical discourse. The analysis also considers the theoretical production of the area of education that directly discusses the purposes of education, focusing the contribution of Anísio Teixeira and Dermeval Saviani to the configuration of Brazilian educational thought during the 20th century, beginning with the examination of the philosophical foundations that sustain their thoughts. Finally, the study ratifies the recognition of the importance of pedagogical tradition as a mediator element, though not taken substantively, and, at the same time, it recognizes the fecundity of some contributions of post-modern thinking to provide contents that establish, even though in a less perennial way, the normativeness of the discourse.